Ethnicity, minority and groups consciousness: an examination of the ethnic group formation of Sri Lankan Muslims through conceptual analysis - Yusoff, Mohammad Agus; Sarjoon, Athambawa; Hussin, Nordin; Zainal Abidin, Mohammad Ghazali; Ahmad, Azhar (Medwell Journals, 2016)
Sri Lankan Muslims form the second ethnic minority in the country. Referred to as ‘Moors’ in academic literature and in official records, they have suffered not only because of ethnic politics but also because of ethnicity discourse in the Sri Lankan context. Even though, Muslims have lived in the area for centuries and have maintained cordial relationships with other ethnic groups, their ethnicity and ethnic group identity has always been questioned and challenged by other major ethnic groups in the country. Beside, these challenges, Muslim revivalists, leaders, scholars and activists have attempted to counter-argue and prove their distinct ethnicity and ethnic group consciousness, throughout history. This study aims to investigate the distinctive features of ethnicity and the historical process of ethnic group consciousness of Sri Lankan Muslims, through, the extensive analysis of relevant concepts which is lacking in the existing literature. This research adopts only secondary data collected from various sources. The results indicate that Sri Lankan Muslims have a clear conceptual basis as well as cultural markers that identify them as a distinct ethnic group demarcating from other ethnic groups.